Epidemiologic trends and geographic patterns of fatal opioid intoxications in Connecticut, USA: 1997-2007. - Green, Traci C; Grau, Lauretta E; Carver, H Wayne; Kinzly, Mark; Heimer, Robert (Drug and alcohol dependence, 2011)
The leading cause of injury death among adults in Connecticut (CT), USA is drug poisonings. We analyzed the epidemiology and geographic distribution of opioid-involved accidental drug-involved intoxication deaths ("overdoses") in CT over an 11-year period.
Keywords: Adolescent; Adult; Analgesics, Opioid; Cause of Death; Connecticut; Female; Heroin; Humans; Male; Methadone; Middle Aged; Narcotics; Opioid-Related Disorders; Overdose; Prescription Drugs; Young Adult